Tantangan Pengelolaan Wisata Berkelanjutan di Taman Narmada Kabupaten Lombok Barat - Rani Angraeni; Hesti Soptiana; Lila Putri; Raden Jufri Azzuri; Ika Wijayanti (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Sustainable Tourism management in the Narmada Park faces significant challengers related to adequate human reseourch. This challenge is one of thr most prominent aspect and needs to be overcome with this right strategy. The research method used is qualitative with case study data analisysis tecniques, then conducting interviews and observation as well as sselecting informants using the purposive sampling technique where the informant is taken with the consideratinon that the informant can represent the research’s goal to obtain accurate information. The results of study show that there are several main challenges, such as inadequate infrastructure and facilities, environmental hygiene problems, and lack of awareness and participation of local communitites. Improvements efforts have been made, but a more targeted staregy is still needed to overcome shese challenges.